2012
DOI: 10.1016/j.vaccine.2012.03.062
|View full text |Cite
|
Sign up to set email alerts
|

The expected emotional benefits of influenza vaccination strongly affect pre-season intentions and subsequent vaccination among healthcare personnel

Abstract: The expected emotional benefits of vaccination strongly affect seasonal influenza vaccination among HCP, even after taking into account other attitudes, pre-season intentions, and prior vaccination history. These attitudes are promising targets for future vaccination campaigns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 44 publications
2
37
1
Order By: Relevance
“…The median age of study participants was 43 years old and the majority were female, white, and non-Hispanic (see [7,9,10] and Supplemental Table). Our analyses focused on FARI episodes among 47 unvaccinated and 174 vaccinated HCP (Supplemental Figure).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The median age of study participants was 43 years old and the majority were female, white, and non-Hispanic (see [7,9,10] and Supplemental Table). Our analyses focused on FARI episodes among 47 unvaccinated and 174 vaccinated HCP (Supplemental Figure).…”
Section: Resultsmentioning
confidence: 99%
“…First, the small sample size prohibited adjustment for covariates such as age and resulted in low estimate precision. Second, it is unclear how previous IIV3 vaccinations and previous natural infections may have influenced our findings, especially given that most study vaccinees had been vaccinated before ( [7,10] and Supplemental Table). Petrie et al [6] may have observed much higher sensitivity among their unvaccinated adults because they were mostly IIV3 naïve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Details on cohort recruitment have been presented previously (Thompson et al, 2012 Demographics and SES measures. The enrollment questionnaire included items on demographics and three indicators of objective SES: education, occupation, and street address, which was used to identify US census block (Table 1).…”
Section: Participantsmentioning
confidence: 99%
“…Previous vaccine receipt, perceived effectiveness, and convenience have all been associated with vaccination [7-10]; with self-protection identified as the primary motivation [11]. Recently, vaccine uptake has been studied in specific populations of community-dwelling children and adults, such as those at higher risk for influenza [9-16].…”
Section: Introductionmentioning
confidence: 99%